EFFECTS OF PHENOLIC COMPOUNDS EXTRACTED FROM SALVIA FRIGIDA ON INDUCED HYPERURICEMIA IN MICE - MUHAMMAD ABDULHUSSEIN AL-DABBAGH; SHIHAB ABDULRAHMAN SHIHAB; ENAS JAWAD KADHIM (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The aim of this study was to investigate effects of phenolic compounds rich fraction extracted from aerial parts of Salvia frigida on serum uric acid (SUA) and xanthine oxidase (XOD) in hyperuricemic mice model. Methods: A total of 40 albino male mice were equally divided into four groups. The blank group was given vehicles only. The model of hyperuricemia was induced by single intraperitoneal injection of UA (250 mg/kg). S. frigida group was pretreated orally with phenolic compounds rich fraction (300 mg/kg) for 6 days and one final oral dose was given directly after the UA injection on the 7th day as an acute treatment and the same was applied to allopurinol (20 mg/kg) which served as a positive control. 1 h later blood was withdrawn to be tested for SUA, XOD, and creatinine levels. Furthermore, the body weights were daily documented before each administration. Results: The results revealed a highly comparable significant reduction in SUA and XOD in both S. frigida and allopurinol groups without significantly affecting serum creatinine compared to model group, also both modestly decreased the body weights of mice. Conclusion: S. frigida significantly reduces SUA in the hyperuricemic model and may also have a promising effect on weight management.